Sexual health promotion interventional program for women undergoing breast cancer treatment: Protocol for a mix-methods study - Sanaz Zangeneh; Mitra Savabi-Esfahani; Fariba Taleghani; Mohammad Reza Sharbafchi; Mehrdad Salehi (Journal of Education and Health Promotion, 2022)
BACKGROUND: Women undergoing breast cancer treatment, especially those of reproductive age, experience sexual health challenges. The aim of this study is to design an interventional program for promoting the sexual health of women undergoing breast cancer treatment. MATERIALS AND METHODS: This is a mixed qualitative-quantitative exploratory study consisting of four phases. In the first phase, the needs and strategies for promoting sexual health of Iranian women with breast cancer in Isfahan city will be identified through a qualitative study. The patients will be selected using purposive sampling method and the data will be collected through semi-structured interviews. In the second phase of the study, the relevant literature will be reviewed. In the third phase, the initial version of the program will be designed based on the results of qualitative study and review of literature, the appropriate strategies are prioritized by the members of the panel of experts, and then, the final interventional program is prepared. In the fourth phase, the designed interventional program will be conducted as a quasi-experimental study in two groups of intervention and control and the effectiveness of the program on sexual quality of life, sexual satisfaction, and sexual function of women undergoing breast cancer treatment will be evaluated. The type of the intervention will be selected based on the results of the previous phases and the opinion of the expert panel. CONCLUSIONS: The results of this study are expected to contribute to the design of an interventional program based on the needs of women undergoing breast cancer treatment and promote health and meet the sexual health needs of breast cancer patients.